2015
DOI: 10.1098/rspb.2015.2151
|View full text |Cite
|
Sign up to set email alerts
|

Health trajectories reveal the dynamic contributions of host genetic resistance and tolerance to infection outcome

Abstract: Resistance and tolerance are two alternative strategies hosts can adopt to survive infections. Both strategies may be genetically controlled. To date, the relative contribution of resistance and tolerance to infection outcome is poorly understood. Here, we use a bioluminescent Listeria monocytogenes (Lm) infection challenge model to study the genetic determination and dynamic contributions of host resistance and tolerance to listeriosis in four genetically diverse mouse strains. Using conventional statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 50 publications
0
58
0
Order By: Relevance
“…; Lough et al. ). Indeed, L. lactis‐ infected flies showed reduced survival at 168 HPI, suggesting that the bacteria or the host immune system damages the host later in the infection.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…; Lough et al. ). Indeed, L. lactis‐ infected flies showed reduced survival at 168 HPI, suggesting that the bacteria or the host immune system damages the host later in the infection.…”
Section: Discussionmentioning
confidence: 98%
“…Disease tolerance tended to improve in mice that survived the initial acute infection phase, which was characterized by pathogen proliferation, and increased resistance in survivors (Lough et al. ). Our study examines tolerance at two timepoints across a range of pathogen densities, where tolerance does indeed change at each timepoint in question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…difference in exposure and onset of infection, differences in the individual immune status, co-infections), which can severely bias tolerance estimates and mask the underlying genetic signal [16, 18]. For this reason, empirical evidence for genetic variation in host tolerance to infections stems primarily from challenge experiments in inbred lines of model species [2, 50, 51]. The PHGC challenge data constitute a unique data source for investigating the genetic basis and relative importance of host resistance and tolerance in outbred pigs’ responses to virus infections, since it provides the required measures of both pathogen load and performance for large sample sizes, without the confounding factors inherent to field data.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent scientific advances have demonstrated that the genetic background of hosts is one of the main drivers of host disease outcomes after exposure to pathogens and is what determines the host tolerance or resistance to infection (e.g. Chapman & Hill, ; Lough, Kyriazakis, Bergmann, Lengeling, & Doeschl‐Wilson, ). Therefore, understanding how inbreeding shapes disease dynamics in wild populations is crucial when considering the design and implementation of management strategies to control infection and limit disease dispersion.…”
mentioning
confidence: 99%